Grassroot democracy in Indian society - Palanithurai, G. (New Delhi, 2000)
Though much emphasis has been given on "Development Administration", both in the Academic world and in the domain of Administration, "Development Politics" has been lost sight of. The gap between the two is narrow and very thin. The former one cannot have any impact in the society without the latter one and vice versa. At present what we see today too much of non issues and very little issues in politics. Yet our polity and administration have got resilience to withstand pressure and manage the crisis, though our political elites and bureaucracy have moved away from good governance. The success and sustenance of our democratic governance is largely the result of the matured behaviour of the people. Often people express their feelings through their ballots and the politicians do understand the feelings and yet they could not mend themselves to act in accordance with the aspirations of the people. There is a block which is invisible between the government and the people. To break the block steps have been taken to decentralise power which will reach even the unreached. This process of decentralization will bring the polity from non-issues to issues, crisis management to development management and Public Administration to Development Administration. The major issues involved in the governing process have been highlighted in this work. It draw lessons mostly from Tamil Nadu. It will help the academics and students to look at governance from the perspective of Development Administration and Development Politics.
Keywords: Democracy India